The Ayyubids: Between Challenge and Identity Struggle – A Study of the Kurdish Confrontation with the Bahri Mamluks - Al-Atroushi, Prof.Dr.Shawkat Arif Muhammad (Sulaimani Journal for Humanities, 2025)
The middle of the seventh century AH/thirteenth century AD witnessed an important political change with the arrival of the Bahri Mamluks, whose emergence posed a direct challenge to the Ayyubids. Especially after they were able to seize power and end the rule of Sultan Turanshah bin AL-Malik AL-Salih Najm AL-Din, the last Ayybubid sultan in Egypt in the year 648AH/1250AD. There is no doubt that the weakness and divisions that afflicted the Ayyubid state after the death of Sultan Saladin, and the immersion of its princes in internal conflicts, weakened their ability to confront the Mamluks, who were able to remove them from power permanently . Internal events, as well as external challenges, played a major role in this change, which had an impact on the course of events and the complex conflicts between the Mamluks and the Kurds in general, because it was not merely a political or military conflict over power, but rather extended to include the identity dimension that was linked to the legacy of the Ayyubids as leaders with Kurdish roots who played a major role in strengthening the Kurdish identity within its general Islamic framework.The Ayyubids expressed this identity through their confrontation with the dominance imposed by the Mamluks , their attempts to maintain their leadership position, and their defense of their cultural and tribal heritage. They also played a major role in the spread of the Kurds and their settlement in different regions, especially in southern Asia Minor, northern Bilad al-Sham , and Egypt, and their emergence in important leadership, administrative, and scientific positions. Realizing the importance of national and religious identity in building and preserving states, especially in multi-ethnic and multi-cultural environments, we decided in this research to shed light on the opposition movements led by the Kurds after the fall of the Ayyubid state, as they were at the forefront of those who rejected Mamluk rule, especially from the Ayyubid family, as they entered into a direct conflict with the Bahri Mamluks in order to restore their political and military role. With an extensive study of the circumstances and factors that caused the failure of their persistent attempts that were not destined to succeed in the face of the Mamluks’ military and organizational strength.
Keywords: The Kurds; the Ayyubids; the Bahri; Mamluks; 7th century AH